Pengaruh Komite Manajemen Risiko, Leverage, dan Umur Perusahaan Terhadap Pengungkapan Enterprise Risk Management (Studi pada Perusahaan Subsektor Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2021) - Alya Ardianti Lahfah; Sri Rahayu (Universitas Batanghari Jambi, 2023)
Enterprise risk management (ERM) disclosure is one of the non-financial information presented in the company’s annual report related to the company’s commitment to managing risk and explaining its future effect. This study aims to determine the effect of risk management committee, leverage, and firm age on enterprise risk management disclosures in banking subsector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2021, either simultaneously or partially. This research uses quantitative methods in the form of secondary data. Banking subsector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2021 are the population in this study. Sampling using purposive sampling technique obtained 136 observation data from 34 company samples with a research period of four years. The data analysis method in this study is panel data regression analysis using Eviews version 12 software. The result of this study indicates that risk management committee, leverage, and firm age simultaneously have a significant effect on enterprise risk management disclosures. Partially, risk management committee, leverage, and firm age have a positive effect on enterprise risk management disclosures. Beside on the result of this study, future researchers are expected to expand the object, period, proxy, and other variables used to test their effect on enterprise risk management disclosures. Companies are adviced to improve the application of enterprise risk management.